PENGARUH MEDIA AUDIOVISUAL TERHADAP HASlL BELAJAR SISWA DALAM PEMBELAJARAN TEMATIK KELAS IV SD - Pangesti, Silvia Mega; Sabri, Tahmid; Kresnadi, Hery (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe problem in this research was â€œHow does the effect of Audiovisual media toward the learning outcomes of thematic learning of four grade student of Elementary School Â 03 Pontianak Kota?â€. The media used in this study was an experimental method to form the study was Quasi Experimental Design, with experimental design Nonequivalent Control Group Design. The sampling technique used non probability sampling with purposive sampling type. Data collection tools used in the form of learning outcomes document and of a written objective-shaped testwith 45 questions. Based on statistical calculations of theÂ  final test experimental class average of 73,57 and learning results of final test control class 65,83, the final test data was obtained at 2,224 and (Î± = 5% and dk 28 + 30 â€“ 2 = 56) amounting to 2,004 because (2,224)>(2,004), then Ha is received. This means that the use Audiovisual media in thematic learning has a moderate influence on the learning outcomes of four grade student of Â Sekolah Elementery School 03 Pontianak Kota.Â Keyword: Audivisual Media, Effects, Learning Outcomes